Noemi Gonda on Patriarchy and climate change - CGIAR Research Program on Climate Change, Agriculture and Food Security (2015)
Patriarchy and climate change: a feminist political ecology of climate change adaptation in rural Nicaragua Presentation by Noemi Gonda, Central European University at the seminar Closing the gender gap in farming under climate change held 19 March 2015 in Paris. Read more about the event: https://ccafs.cgiar.org/events/closing-gender-gap-farming-under-climate-change-new-knowledge-renewed-action